Analisis Pengamatan Parameter Fisika Biologi Pada Kolam Budidaya Ikan LeleDumbo (Clarias Garipinus) - Marlus Aval Adi Nazara; Wiraswasty Nazara (CV. SINAR HOWUHOWU, 2024)
The technology used in catfish (Lele) farming is not a hindrance, but requires diligence in monitoring all changes in air quality as the medium for cultivating the fish, in addition to feeding. The water source used for maintaining the catfish must meet the required physical and chemical parameters of the air. The physical properties of the air serve as the living environment and provide space for the fish to move. The chemical properties of the air provide essential elements, ions, dissolved gases, pH, and others. These conditions must meet the requirements necessary for the life and growth of the cultivated fish. The quality of the air determines the success of the survival and growth of the catfish, as the air is the medium in which the catfish live. If the water becomes polluted, it will interfere with the growth of the cultivated catfish. Based on this, an observation was made on